Increasing consumers’ hypermarket visit intention through cause-related marketing: a perspective from the theory of planned behaviour - Hong, Kay Tze; Siew, Imm Ng; Raja Yusof, Raja Nerina; Kaliappan, Shivee Ranjanee (Fundacao Escola de Comercio Alvares Penteado, 2019)
Purpose: This study intends to discover factors affecting consumers’ intention to participate in cause-related marketing (CRM) and how CRM influences their intention to visit hypermarkets in Malaysia. Design/methodology/approach: Through a self-administered questionnaire and using a mall-intercept technique, a total of 460 samples were collected from consumers in Malaysia. Structural equation modelling was then used to analyse the data. Findings: The results show that three variables (perceived CSR image, consumer-company identification and perceived company-cause fit) out of four significantly predicted consumers’ attitude towards CRM. Also, two components (attitude and perceived behavioural control) out of three in the theory of planned behaviour were found to be significantly related to CRM participation intention. Lastly, CRM participation intention was found to influence hypermarket visit intention. Originality/value: The proposed theory of planned behaviour (TPB) was found to be applicable in predicting CRM participation intention and hypermarket visit intention. The findings showed that consumers are more likely to increase their intention to visit a hypermarket that adopts a CRM campaign, which led us to highlight the main implications for hypermarket management and new study areas in this field.